Implementation Strategies to Enhance Youth-Friendly Sexual and Reproductive Health Services in Sub-Saharan Africa: A Systematic Review - Obiezu-Umeh, Chisom; Nwaozuru, Ucheoma; Mason, Stacey; Gbaja-Biamila, Titilola; Oladele, David; Ezechi, Oliver; Iwelunmor, Juliet (Frontiers in Reproductive Health, 2021)
Introduction: Youth-friendly health service (YFHS) interventions are a promising, cost-effective approaches to delivering sexual and reproductive services that cater to the developmental needs of young people. Despite a growing evidence-base, implementation of such interventions into practice have proven to be challenging in sub-Saharan Africa (SSA). Thus, the purpose of this review is to synthesize existing evidence on YFHS implementation in SSA and understand which implementation strategies were used, in what context, how they were used, and leading to which implementation outcomes. Methods: A comprehensive literature search in PubMed, Embase, Scopus, and CINAHL, was conducted to identify peer-reviewed research articles published from database inception up until August 2020. Eligible studies were required to include young people (ages 10–24 years) in sub-Saharan Africa. Studies that described implementation strategies, as conceptualized by the Expert Recommendations for Implementing Change (ERIC) project, used to enhance the implementation of YFHS were included. Implementation outcomes were extracted using Proctor and colleagues' 8 taxonomy of implementation outcomes. Results: We identified 18 unique interventions (reported in 23 articles) from an initial search of 630 articles, including seven from East Africa, seven from South Africa, and four from West Africa. In most studies (n = 15), youth-friendly health services were delivered within the context of a health facility or clinic setting. The most frequently reported categories of implementation strategies were to train and educate stakeholders (n = 16) followed by infrastructure change (n = 10), to engage consumers (n = 9), the use of evaluative and iterative strategies (n = 8), support clinicians (n = 8), and providing interactive assistance (n = 6). The effectiveness of the strategies to enhance YFHS implementation was commonly measured using adoption (n = 15), fidelity (n = 7), acceptability (n = 5), and penetration (n = 5). Few studies reported on sustainability (n = 2), appropriateness (n = 1), implementation cost (n = 1) and feasibility (n = 0). Conclusion: Results of the review emphasize the need for further research to evaluate and optimize implementation strategies for promoting the scale-up and sustainability of evidence-based, YFHS interventions in resource-constrained settings. This review also highlights the need to design robust studies to better understand which, in what combination, and in what context, can implementation strategies be used to effectively enhance the implementation of YFHS interventions.